Attachment to inanimate objects and early childcare: A twin study - Fortuna, Keren; Baor, Liora; Israel, Salomon; Abadi, Adi; Knafo, Ariel (Frontiers in Psychology, 2014)
Extensive nonmaternal childcare plays an important role in children's development. This study examined a potential coping mechanism for dealing with daily separation from caregivers involved in childcare experience—children's development of attachments toward inanimate objects. We employed the twin design to estimate relative environmental and genetic contributions to the presence of object attachment, and assess whether childcare explains some of the environmental variation in this developmental phenomenon. Mothers reported about 1122 3-year-old twin pairs. Variation in object attachment was accounted for by heritability (48%) and shared environment (48%), with childcare quantity accounting for 2.2% of the shared environment effect. Children who spent half-days in childcare were significantly less likely to attach to objects relative to children who attended full-day childcare.